Ecosystem response to earlier ice break‐up date: Climate‐driven changes to water temperature, lake‐habitat‐specific production, and trout habitat and resource use. (5th August 2020) - Caldwell, Timothy J.; Chandra, Sudeep; Feher, Karly; Simmons, James B.; Hogan, Zeb
Abstract: Climate warming has yielded earlier ice break‐up dates in recent decades for lakes leading to water temperature increases, altered habitat, and both increases and decreases to ecosystem productivity. Within lakes, the effect of climate warming on secondary production in littoral and pelagic habitats remains unclear. The intersection of changing habitat productivity and warming water temperatures on salmonids is important for understanding how climate warming will impact mountain ecosystems. We develop and test a conceptual model that expresses how earlier ice break‐up dates influence within lake habitat production, water temperatures and the habitat utilized by, resources obtained and behavior of salmonids in a mountain lake. We measured zoobenthic and zooplankton production from the littoral and pelagic habitats, thermal conditions, and the habitat use, resource use, and fitness of Brook Trout ( Salvelinus fontinalis ). We show that earlier ice break‐up conditions created a "resource‐rich" littoral–benthic habitat with increases in zoobenthic production compared to the pelagic habitat which decreased in zooplankton production. Despite the increases in littoral–benthic food resources, trout did not utilize littoral habitat or zoobenthic resources due to longer durations of warm water temperatures in the littoral zone. In addition, 87% of their resources were supported by the pelagic habitat during periods with earlier ice break‐up when pelagic resources were least abundant. The decreased reliance on littoral–benthic resources during earlier ice break‐up caused reduced fitness (mean reduction of 12 g) to trout. Our data show that changes to ice break‐up drive multi‐directional results for resource production within lake habitats and increase the duration of warmer water temperatures in food‐rich littoral habitats. The increased duration of warmer littoral water temperatures reduces the use of energetically efficient habitats culminating in decreased trout fitness. Abstract : Earlier ice break‐up dates are occurring with climate change. We find that earlier ice break‐up dates in mountain lakes are increasing the duration of warm stratified waters limiting access to the productive littoral zone for fish. During these years fish forage in the pelagic zone where we find decreasing levels of zooplankton production related to early ice break‐up. The changes we describe to the thermal regime and habitat specific invertebrate productivity culminate in lower fish fitness.